2016
DOI: 10.1111/ijd.13232
|View full text |Cite
|
Sign up to set email alerts
|

Sweet's syndrome: a retrospective study of 90 cases from a tertiary care center

Abstract: To the best of the present authors' knowledge, this is the largest series of SS to be reported. Clinical presentations are similar to those described in the literature. Colchicine was efficient and facilitates the reduced use of corticosteroids. The association between SS and neoplasms should be considered in the context of vesiculobullous lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 22 publications
3
28
1
8
Order By: Relevance
“…This notion has been supported by two findings: 1) blood vessels in lesions of longer duration are more likely to develop vasculitis than those in lesions of shorter duration, likely due to prolonged exposure to noxious metabolites; 2) immunofluorescence studies show no immunoglobulin and complement deposition in the affected blood vessels. Many authors have therefore concluded that the presence of vasculitis ought not to rule out the diagnosis of SS unless there is evidence of primary immune‐mediated vasculitis . In this context, we believe that the clinical features of SS are critical for the diagnosis as the presence of typical SS lesions strongly suggests vasculitis – reported in some cases of SS – to be a secondary event, given that primary immune‐mediated leukocytoclastic vasculitis presents with lesions clinically completely different from those observed in SS.…”
Section: Discussionmentioning
confidence: 93%
“…This notion has been supported by two findings: 1) blood vessels in lesions of longer duration are more likely to develop vasculitis than those in lesions of shorter duration, likely due to prolonged exposure to noxious metabolites; 2) immunofluorescence studies show no immunoglobulin and complement deposition in the affected blood vessels. Many authors have therefore concluded that the presence of vasculitis ought not to rule out the diagnosis of SS unless there is evidence of primary immune‐mediated vasculitis . In this context, we believe that the clinical features of SS are critical for the diagnosis as the presence of typical SS lesions strongly suggests vasculitis – reported in some cases of SS – to be a secondary event, given that primary immune‐mediated leukocytoclastic vasculitis presents with lesions clinically completely different from those observed in SS.…”
Section: Discussionmentioning
confidence: 93%
“…A dose of 1–2 mg per day was used with regression of lesions in 1–14 days in 30 patients (68%) receiving the drug. Of the 13 patients who did not respond to colchicine initially, there was improvement following the addition of prednisone …”
Section: Potential Indications: the Newmentioning
confidence: 99%
“…Patients are febrile and present erythematous welldefined and asymmetrical plaques or papules on the skin [46]. Histopathology shows absence of vasculitis, a diffuse perivascular and nodular neutrophilic infiltrate, and various degrees of edema [46,47]. Mucosal involvement is rare.…”
Section: Differential Diagnosismentioning
confidence: 99%